An Analysis of the Impact of Health on Occupation - Flavel, Joanne (My University, 2016)
Maintaining individuals with health limitations in the labour force is a challenge of increasing importance given the ageing of the population. Determining the effect of health on occupation may tell us how people adapt to their limitations, and what types of jobs make this harder or easier. This paper uses the first 14 waves of the Household, Income and Labour Dynamics in Australia Survey (HILDA) to examine the effect of health and changes in health on occupation for the working-age population. We use dynamic panel models which account for selection into employment. Two measures of occupation are used to capture two aspects of occupation highlighted in the literature as being linked to health: physical job demands and status. The results of the analyses provide some evidence that a health shock reduces the likelihood of manual employment for men, suggesting that men may adapt to a health shock by reducing physical job demands. Worsening health and work-limiting long-term conditions are found to have a negative effect on occupational status for men and women, suggesting health selection into lower-status jobs, and an adverse effect of poor health on occupational mobility.
NILS Working Paper
Keywords: Health; Employment; Labour market; Health and wellbeing; Health; Employment; Employment and unemployment; Health and wellbeing